Proceedings from the Third International Post-Tuberculosis Symposium: expanding the circle. - Allwood,BW; Auld,SC; Beko,B; Bisson,GP; Borges,de Almeida CP; Byrne,A; Chow,FC; Davis,A; Defres,S; Drage,M; Evans,D; Gai,X; et al. (IJTLD Open, 2025)
In light of the recent growth in interest and knowledge of post-TB sequelae, there were high levels of engagement during the 3rd International Post-Tuberculosis Symposium held in Stellenbosch, South Africa. This multi-disciplinary symposium aimed to: 1) Advocate for greater global awareness of post-TB sequelae and empower TB-affected communities; 2) Advance knowledge by sharing current evidence and identifying key priorities; 3) Foster collaborations by strengthening research networks and developing concrete plans for research driven advocacy; and 4) Advance the field by establishing areas of consensus around diagnosis, care, and management. Guided by a 14-member Steering Committee, 9 academic working groups came together to develop key content for plenary sessions and facilitated workshops related to: Patient Engagement, Epidemiology and Modelling, Pathogenesis, Post-TB Lung Disease; Cardiovascular and Pulmonary Vascular Disease; Central Nervous System and Musculoskeletal Disease; Paediatrics Economic; Social and Psychological Sequelae; and Advocacy, Policy, and Stakeholder Engagement. Each group outlined progress within their respective fields and defined key priorities to focus discussion. The Symposium further catalysed coordinated action for the post-TB community of patients, advocates, clinicians, and researchers to define a clear path towards improving outcomes, reducing inequities, and ensuring TB survivors receive the care and support they deserve.